FLUID DYNAMIC SIMULATION ON THE FLARE OF COMBUSTION OF GAS FROM BIOMASS GASIFICATION - susanto, dian; Kosim, Muhtar; Wibowo, Ari (Universitas Majalengka, 2023)
The use of energy which always comes from fossil fuels will eventually run out, so the development of renewable energy or alternative energy is very important to maintain petroleum reserves and as a substitute for fossil fuels which are the main energy source. One alternative energy is biomass which has not been widely used by the gasification method. The gas produced by the gasification process is utilized by burning it in a flare to get a flame. In this study, the 3D simulation method with Computational Fluid Dynamics (CFD) was used to determine the temperature distribution on the flare walls using CFD simulations and to compare the temperature of the flare walls from the CFD simulation results with the test results. The results of this study, the distribution of combustion occurs in the flare with a temperature of 1106°C in the upper area close to the outlet boundary. The wall temperature comparison shows that the CFD simulation tends to be similar to the test results. This shows that computational fluid dynamic simulations can be used to predict fluid flow rates and combustion reactions.